Impact of HLA compatibility in recipients of kidneys from expanded criteria donors: a Collaborative Transplant Study Report - Echterdiek, Fabian Friedrich; Latus, Jörg; Döhler, Bernd; Schwenger, Vedat; Süsal, Caner (International journal of immunogenetics, 2021)
Due to a widespread organ shortage, the use of expanded criteria donors (ECDs) in kidney transplantation has increased persistently, reaching approximately 40% in recent years. Whether human leucocyte antigen (HLA) matching between donor and recipient should be part of allocation algorithms in transplantation of ECD kidneys, and especially of ECD kidneys from ≥70-year-old donors, is still in question. To this end, 135,529 kidney transplantations performed between 2000 and 2017 and reported to the Collaborative Transplant Study were analysed and the impact of HLA-A+B+DR mismatches on death-censored graft and patient survival as well as on rejection episodes was investigated. Results were stratified according to donor status (standard criteria donor (SCD) versus ECD) and age of ECD. HLA incompatibility increased the five-year death-censored graft failure risk similarly strong in recipients of ECD and SCD transplants (hazard ratio (HR) per HLA mismatch 1.078 and 1.075, respectively; p < .001 for both). Its impact on rejection treatments during the first post-transplant year was also significant but slightly weaker for recipients of ECD transplants (risk ratio (RR) per HLA mismatch 1.10 for ECD transplants and 1.13 for SCD transplants; p < .001 for both). Mortality increased gradually from zero to six HLA mismatches in recipients of SCD transplants, whereas for ECD transplants a significant increase was notable only from zero to more than zero mismatches. A significant but slightly less pronounced impact of HLA incompatibility on graft failure was observed in transplants from ≥70- compared with <70-year-old ECDs (HR per mismatch 1.047 and 1.093; p = .009 and < 0.001, respectively). The influence of HLA mismatches on rejection treatments was the same for both ECD age groups (RR = 1.10, p < .001 and p = .004, respectively). Our data indicate that HLA matching should be part of allocation algorithms not only in transplantation of kidneys from SCDs but also from ECDs.
Zuerst publiziert: 17. September 2020
Gesehen am 25.09.2025